Evaluation of the American Society of Anesthesiologists Physical Status Classification System in Risk Assessment for Lower Extremity Reconstruction with Free Tissue Transfer - Maldonado, Andrés A.; Steinebach, Rabanus; Morillo, M. Carmen; Sauerbier, Michael (Journal of Reconstructive Microsurgery, 2021)
Background The applicability of free flap reconstruction for lower extremity (LE) defects in high-risk patients continues to require ongoing review. The aim of this study was to analyze the risk factors, management, and outcome of LE free flap reconstruction in high-risk (American Society of Anesthesiologists [ASA] class 3 or 4) patients.Methods A retrospective chart review was performed for all patients who underwent LE reconstruction in our Institution (Level I Trauma Center) from 2013 to 2019. Medical records and the authors' prospectively maintained database were analyzed with respect to ASA class, comorbidities, and postoperative complications. All patients were treated using the same pre-, intra-, and postoperative multidisciplinary approach.Results A total of 199 patients were analyzed. Sixty-six flaps were transferred in 60 patients with an ASA class 3 or higher. High-risk patients did not present a higher rate of flap loss or LE amputation. The overall flap success rate was 92%. There were five flap losses in high-risk patients. Three of these five patients underwent a successful second free flap reconstruction. The overall success rate of LE reconstruction in high-risk patients was 90%. Four patients with successful free flap ended up in LE amputation due to bone infection and two patients underwent an amputation after the first free flap failure.Conclusion Free flap reconstruction for LE defects in high-risk patients is a safe and reliable procedure for selected patients when an experienced multidisciplinary team is involved. Bone infection was the only variable associated with LE amputation.
Keywords: lower extremity; microsurgery; free flap; high-risk patients; ASA classification